PENGARUH METODE PENGERINGAN PADA MUTU FISIK MINUMAN HERBAL CELUP DENGAN KOMPOSISI JAHE, TEMULAWAK, KUNYIT DAN SEREH - Husnani Husnani; Nur Aidil Fitri Nur Aidil Fitri (Bajang Institute, 2022)
This study aims to obtain a method of drying simplicia based on the physical quality of a dipped herbal powder drink with a composition of ginger, temulawak, turmeric and lemongrass. The physical quality values ​​included organoleptic, soluble time, water content and the panelists' preference for herbal drinks with the composition of ginger, temulawak, turmeric and lemongrass. The research was carried out experimentally using a variety of drying methods, namely drying in an incubator at a temperature of 60°C, drying in an oven at a temperature of 100°C, and drying in the sun with 3 replications each. The results showed that the water content of the simplicia used the drying method with an incubator at 60°C (8%), drying in an oven at 100°C (16%), drying in the sun (5.6%). The dissolving time of the drink used the drying method with an incubator at 60°C (129 seconds), drying in an oven at 100°C (74 seconds), drying in the sun (77 seconds). The total score of the panelists' preference for the color, aroma and taste of the drink was drying in an incubator at a temperature of 60°C (258), drying in an oven at 100°C (258), drying in the sun (249). Based on the physical quality, the best dipped herbal powder drink and preferred by the panelists was the dipped herbal powder drink with the composition of ginger, temulawak, turmeric and lemongrass by drying using an incubator at 60°C.